Patterns, trigonometry, calculators and calculus - Dobbs D.E. (1990)
I wish to thank Professor A. Shenitzer (York University, Canada) and Professor R. Jean (Universite du Quebec a Rimouski, Canada) for kindly reading this paper and making many valuable suggestions. This work has been supported by the Peruvian Council of Science and Technology (CONCYTEC).